2020
DOI: 10.3390/jcm9040997
|View full text |Cite
|
Sign up to set email alerts
|

Wear in Antagonist Teeth Produced by Monolithic Zirconia Crowns: A Systematic Review and Meta-Analysis

Abstract: Background: The aim of this systematic review and meta-analysis was to determine the wear sustained in the natural antagonist tooth in cases of full-coverage fixed-base prosthetic restorations or monolithic zirconia tooth-supported crowns, as well as to determine the wear in the restoration itself, both in the short- and medium-term and considering the factors that may influence wear. Material and methods: A systematic literature review and meta-analysis, based on Preferred Reporting Items for Systematic Revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…One restoration showed a loss of occlusion in one abutment tooth because of wear at the occlusal surface that could be due to a loss of the surface coating of the glass resulting in an increased surface roughness 68 . The wear of monolithic zirconia restorations was previously reported, and several factors may be involved such as the surface treatment (glazed or polished), the position of the restorations, or surface roughness 33,36,68–71 . However, previous study reported that zirconia wear, either in vitro or clinical, is normally negligible 69 …”
Section: Discussionmentioning
confidence: 97%
“…One restoration showed a loss of occlusion in one abutment tooth because of wear at the occlusal surface that could be due to a loss of the surface coating of the glass resulting in an increased surface roughness 68 . The wear of monolithic zirconia restorations was previously reported, and several factors may be involved such as the surface treatment (glazed or polished), the position of the restorations, or surface roughness 33,36,68–71 . However, previous study reported that zirconia wear, either in vitro or clinical, is normally negligible 69 …”
Section: Discussionmentioning
confidence: 97%
“…One previously reported flaw of monolithic zirconia crowns is that, given the superior hardness of the material (Hv ≈ 1200 GPa; double that of porcelain [ 34 ]), zirconia could be more abrasive to enamel than other restorative materials, at least on paper, especially if not polished properly [ 35 ]; recent systematic reviews have concluded though that monolithic zirconia is not more abrasive than other, commonly used, restorative materials, at least in in vitro studies [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Polished monolithic zirconia crowns showed no accelerated wear compared with metal-ceramic crowns [74]. Solá-Ruíz et al [75] additionally included three newer studies [76][77][78]. With follow-up times varying between 6 and 24 months, a high degree of heterogeneity was found in the meta-analysis.…”
Section: Antagonist Enamel Wearmentioning
confidence: 99%